Reversible Humidity-Driven Transformation of a Bimetallic EuCo Molecular Material: Structural, Sorption, and Photoluminescence Studies - Jakub J. Zakrzewski; Michal Heczko; Robert Jankowski; Szymon Chorazy (Molecules, 2021)
Functional molecule-based solids built of metal complexes can reveal a great impact of external stimuli upon their optical, magnetic, electric, and mechanical properties. We report a novel molecular material, {[EuIII(H2O)3(pyrone)4][CoIII(CN)6]}·nH2O (1, n = 2; 2, n = 1), which was obtained by the self-assembly of Eu3+ and [Co(CN)6]3− ions in the presence of a small 2-pyrrolidinone (pyrone) ligand in an aqueous medium. The as-synthesized material, 1, consists of dinuclear cyanido-bridged EuCo molecules accompanied by two H-bonded water molecules. By lowering the relative humidity (RH) below 30% at room temperature, 1 undergoes a single-crystal-to-single-crystal transformation related to the partial removal of crystallization water molecules which results in the new crystalline phase, 2. Both 1 and 2 solvates exhibit pronounced EuIII-centered visible photoluminescence. However, they differ in the energy splitting of the main emission band of a 5D0 → 7F2 origin, and the emission lifetime, which is longer in the partially dehydrated 2. As the 1 ↔ 2 structural transformation can be repeatedly reversed by changing the RH value, the reported material shows a room-temperature switching of detailed luminescent features including the ratio between emission components and the emission lifetime values.